Educational Program for Introduction to Tactile Cartographic Language and introduction to map reading in the regular classroom (Práxis Educativa, 2023)
This article, based on a doctoral dissertation, has as general objective to analyze the effects of the Educational Program for Introduction to Tactile Cartographic Language, when applied in the context of a regular classroom, with blind students. To this end, a qualitative, exploratory research of a descriptive nature was carried out, characterized by an intervention. The following data collection instruments were used: open questionnaire, survey, interview, field diary and the intervention program. The data were subjected to the descriptive analysis. The development of this study showed that the mentioned program can and should be developed by teachers with all students in the regular classroom.Keywords: Special Education. Blindness. Tactile cartography.